A doubly interpenetrated layer structure: 4-Acetamidobenzaldehyde 4-Nitrophenylhydrazone - de Lima, G.M.; Wardell, S.M.S.V.; Wardell, J.L.; Tiekink, E.R.T. (Kluwer (now part of Springer), 2010)
The title molecule, 4-acetamidobenzaldehyde 4-nitrophenylhydrazone, is essentially planar with the maximum deviations from the least-squares plane through the 22 non-hydrogen atoms being 0.176(1)angstrom (nitro-O) and -0.152(1) angstrom(amide-O). The dihedral angle between the benzene rings is 6.93(7)degrees. The conformation about the C=N bond is E. The presence of amide-H center dot center dot center dot O-nitro and hydrazine-H center dot center dot center dot O-amide hydrogen bonding leads to the formation of zigzag 2-D arrays with a pseudo three-connected brick-wall network when viewed normal to the plane of the layer. The layers are sustained by 38-membered {center dot center dot center dot OCNC5N2C4NO center dot center dot center dot HNCO center dot center dot center dot HN2C5NH center dot center dot center dot ONC4NH} synthons and the rather large voids defined by these are occupied by a centrosymmetrically related layer to result in the formation of a doubly interpenetrated network. These stack along the b direction being connected by C-H center dot center dot center dot O interactions. The compound crystallizes in the monoclinic space group P2(1)/c with a = 10.8152(3) angstrom, b = 10.9469(2) angstrom, c = 12.9198(4) angstrom, beta = 113.679(1)degrees, and Z = 4.